Concept of Automated Agriculture - Auto Techno Farming. Issue 1 (February 2021) - Sharath Prasanna, R.; Karthikeyan, V.; Mohamed Armoon Shaliq, M.; Sarath, ARP
Abstract: Agriculture cushions men and helps humans to lead a comfortable and convenient life. The main objective of this project is to enhance farm productivity in large scale farming and urban areas, it tends to solve the uncertain issues that are developing in urban agriculture by implementing human free automated agriculture. With the espousal of Artificial Intelligence in Auto Techno Farming (ATF) can lead to the development of advanced agricultural farming methods. We are presenting the concept of automated agriculture that is a track based farming technique for large area farming. Machine design is carried out in such a way that it receives a single command from the user, after which it assesses and analyses geographical conditions and begins to send the analysed data to the user. ATF is fully automated, which will assist to select the seeds by itself and sow the seed according to the optimal weather conditions in appropriate time. The challenging issue probably solved by ATF is, it sprays pesticide only to the required areas. In addition this provides multitudinous advantages such as, full automation, uses AI, weeding, harvesting and other farming techniques are done predominantly by itself. The project proposed above can be tested on agricultural fields with high precision. It makes a pristine beauty of agriculture and makes the survival of the man significant by ATFs. ATF serves as a milestone in the field of agriculture under emerging Environmental Engineering Technologies. The concept of Auto Techno farming is described with the design, simulation and circuits out of CATIA V5, Creo, MATLAB, Proteus 8.9 and Blender.